EXPLORING GEN Z SLANG IN SNL’s ‘GEN Z HOSPITAL’ YOUTUBE SKETCH: A SEMANTIC STUDY (Argopuro: Jurnal Ilmu Bahasa, 2025)
Amidst the rapidly developing digital era, especially among younger generation, Gen Z has developed a variety of slang terms that reflect their perspectives on life, humor, and online culture. This study examines the use of Gen Z slang in the “Gen Z Hospital” sketch aired by Saturday Night Live on YouTube. Using qualitative method, the study evaluates how these slang expressions represent the varied characteristics featured on Gen Z linguistic communication. Data were collected by transcribing dialogues in the sketch. As a theoretical basis, Chapman's (1988) primary slang theory was used, which views slang as a form of informal language that develops naturally in subcultural groups. Semantic analysis was applied to comprehend the meaning, function, and contextual use of the identified slang. The researcher found and separated several types of slang, including clipping is found 3 data, compounding is found 2 data, imitative is found 1 data, fresh and creative is found 12 data, and flippant is found 19 data. This investigation provides valuable insights aimed at educators, linguists, and media analysts in understanding the influential language patterns of today's youth popular culture that are constantly changing and have a strong cultural influence.Keywords: gen z, slang, Youtube. AbstrakDi tengah pesatnya perkembangan era digital, khususnya di kalangan generasi muda, Generasi Z telah menciptakan beragam istilah bahasa gaul yang mencerminkan sudut pandang mereka terhadap kehidupan, humor, dan budaya daring. Penelitian ini mengkaji penggunaan bahasa gaul Gen Z dalam sketsa “Gen Z Hospital” yang ditayangkan oleh Saturday Night Live di kanal YouTube resminya. Dengan menggunakan metode kualitatif, studi ini mengevaluasi bagaimana ekspresi bahasa gaul tersebut merepresentasikan karakteristik linguistik yang beragam dalam komunikasi Gen Z. Data dikumpulkan melalui transkripsi dialog dalam sketsa tersebut. Sebagai landasan teori, digunakan teori primary slang dari Chapman (1988) yang memandang slang sebagai bentuk bahasa informal yang berkembang secara alami di dalam kelompok subkultural. Analisis semantik diterapkan untuk memahami makna, fungsi, dan penggunaan kontekstual dari slang yang teridentifikasi. Peneliti menemukan dan mengelompokkan beberapa jenis slang, antara lain: clipping sebanyak 3 data, compounding 2 data, imitative 1 data, fresh and creative 12 data, dan flippant 19 data. Penelitian ini memberikan wawasan yang berharga bagi pendidik, ahli linguistik, dan analis media dalam memahami pola bahasa populer anak muda masa kini yang bersifat dinamis dan memiliki pengaruh budaya yang kuat.Kata kunci: gen z, gaul, slang, Youtube.